5
$\begingroup$

Please help me to evaluate the following

$$\sum\limits_{n=1}^\infty \frac{\left(\frac{3-\sqrt{5}}{2}\right)^n}{n^3}$$

Have no idea how to evaluate. Any trick please?

Thanks

$\endgroup$
  • $\begingroup$ The only thing I noted is that $3-\sqrt{5}=\dfrac{1}{2}\left(\sqrt{5}-1\right)^2$ but I don't know how it can be helpful. $\endgroup$ – user 170039 Dec 5 '14 at 9:22
  • $\begingroup$ This is a polylogarithm and in this specific case it may be simplified as shown by Alpha. $\endgroup$ – Raymond Manzoni Dec 5 '14 at 9:31
  • $\begingroup$ You can prove by induction that $\Bigl(\dfrac{3-\sqrt{5}}{2}\Bigr)^n=\dfrac{A_n+B_n\sqrt{5}}{2}$ where $$A_0=2,\;\;A_1=3,\;\;A_n=A_{n-1}+A_{n-2}\\[0.1in] B_0=0,\;\;B_1=-1,\;\;B_n=B_{n-1}+B_{n-2}$$ though again, I'm not sure this helps at all. $\endgroup$ – Sal Dec 5 '14 at 9:35
6
$\begingroup$

Differentiating: $\displaystyle f(z) = \operatorname{Li}_{3}(z) + \operatorname{Li}_{3}(1-z)+ \operatorname{Li}_{3}\left(1 - \frac{1}{z}\right)$

We have, $\displaystyle f'(z) = \frac{\operatorname{Li}_2(z)}{z} - \frac{\operatorname{Li}_2(1-z)}{1-z} +\frac{\operatorname{Li}_2\left(1 - \frac{1}{z}\right)}{1 - \frac{1}{z}}.\left(\frac{1}{z^2}\right)$

Using the reflection formula and Abel Identity as indicated here we have,

$\displaystyle \operatorname{Li}_2(z)-\operatorname{Li}_2\left(1 - \frac{1}{z}\right)=\zeta(2)-\ln z\ln(1-z)+\frac12\ln^2 z$

$\displaystyle \operatorname{Li}_2(1-z)+\operatorname{Li}_2\left(1 - \frac{1}{z}\right)=-\frac12\ln^2z$

Since, $$\displaystyle \begin{align}f'(z) &= \frac{\operatorname{Li}_2(z)}{z} - \frac{\operatorname{Li}_2(1-z)}{1-z} +\frac{\operatorname{Li}_2\left(1 - \frac{1}{z}\right)}{1 - \frac{1}{z}}.\left(\frac{1}{z^2}\right) \\ &= \frac{\operatorname{Li}_2(z)-\operatorname{Li}_2\left(1-\frac{1}{z}\right)}{z}-\frac{\operatorname{Li}_2(1-z)+\operatorname{Li}_2\left(1-\frac{1}{z}\right)}{1-z} \\ &=\frac{\zeta(2)-\ln z\ln(1-z)}{z}+\frac{\ln^2 z}{2z} + \frac{\ln^2 z}{2(1-z)} \tag{1}\end{align}$$

We can differentiate $\displaystyle g(z) = \zeta(3) + \frac{\ln^{3} (z)}{6}+ \frac{\pi^{2} \ln (z) }{6}- \frac{\ln^{2} (z) \ln(1-z)}{2}$ and see that it is equal to $f'(z)$, and it agrees with $f(z)$ at $z=1$, i.e., $g(1) = f(1) = \zeta(3)$.

Alternatively, direct integration of $(1)$ yields $g(z)$.

Hence, $\displaystyle \operatorname{Li}_{3}(z) + \operatorname{Li}_{3}(1-z)+ \operatorname{Li}_{3}\left(1 - \frac{1}{z}\right) = \zeta(3) + \frac{\ln^{3} (z)}{6}+ \frac{\pi^{2} \ln (z) }{6}- \frac{\ln^{2} (z) \ln(1-z)}{2}$

Now, to compute $\operatorname{Li}_3(\xi)$, where, $\displaystyle \xi = \frac{3-\sqrt{5}}{2}$ we observe, $\displaystyle \xi^2 - 3\xi + 1= 0 \implies \frac{-\xi}{1-\xi} = -(1-\xi)$

and,

$\displaystyle \begin{align} &f(1-\xi) \\&= \operatorname{Li}_3(\xi) + \operatorname{Li}_3(1-\xi)+\operatorname{Li}_3\left(\frac{-\xi}{1-\xi}\right) \\&= \operatorname{Li}_3(\xi) + (\operatorname{Li}_3(1-\xi) + \operatorname{Li}_3(-(1-\xi))) \tag{2}\\&= \operatorname{Li}_3(\xi) + \frac{1}{4}\operatorname{Li}_3((1-\xi)^2) \\&= \frac{5}{4}\operatorname{Li}_3(\xi) \end{align}$

In step $(2)$, we used: $\displaystyle \operatorname{Li}_3(z)+\operatorname{Li}_3(-z) = \frac{1}{4}\operatorname{Li}_3(z^2)$

Equating and simplifying with $\xi = \phi^{-2}$ yields $\displaystyle \operatorname{Li}_3(\phi^{-2})= \frac{4}{5}\zeta(3)+\frac{2}{3}\log^3\phi-\frac{2\pi^2}{15}\log\phi.$

$\endgroup$
2
$\begingroup$

Your series is a special value of the trilogarithm function.

Through Landen's identities it is not difficult to prove that:

$$\operatorname{Li}_3\left(\frac{1}{\phi^2}\right)= \frac{4}{5}\zeta(3)+\frac{2}{3}\log^3\phi-\frac{2\pi^2}{15}\log\phi.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.